Dataset: Spatial Variability of Soil Greenhouse Gas Emissions in Oil Palm Plantation under Different Management Zones - Sakrabani, Ruben; Chang, Yu Yang; Golicz, Karolina K.; Kim, Sang Yoon; Tan, Ngai Paing; Sim, Choon Cheak (Cranfield University, 2026)
As global demand for palm oil continues to rise, improving the accuracy of greenhouse gas (GHG) accounting in oil palm plantations is essential for evaluating their environmental sustainability. In this study, we assessed soil CO2, N2O, and CH4 emissions across three principal management zones in a mature oil palm (nine-year-old) plantation cultivated in mineral soils- frond heap (FH), palm circle (PC), and harvesting path (HP) under standard operational practices. Soil GHG fluxes were measured using static chambers coupled with a Fourier-transform infrared (FTIR) gas analyser, alongside surface soil (0–5 cm) sampling to characterise soil organic carbon, total nitrogen, moisture content, bulk density, porosity, and pH. In total, 90 measurement points were evaluated to capture within-plantation spatial variability. The FH zone exhibited significantly higher soil organic carbon, total nitrogen, porosity, and moisture content, and lower bulk density than the PC and HP zones. These properties translated into significant higher mean GHG fluxes in FH soils, with CO2, N2O, and CH4 emissions of 165.7 mg m-2 h-1, 0.25 mg mg m-2 h-1, and 0.25 mg m-2 h-1, respectively. In contrast, HP soils were more compacted, carbon-poor, and exhibited the lowest GHG emissions.
Keywords: Greenhouse gas; soil emission; soil organic carbon; oil palm; plant residue